Time to poor treatment outcome and its predictors among drug-resistant tuberculosis patients on second-line anti-tuberculosis treatment in Amhara region, Ethiopia: retrospective cohort study - Daniel Bekele Ketema; Kindie Fentahun Muchie; Asrat Atsedeweyn Andargie (BMC, 2019)
Abstract Background Treatment of drug-resistant tuberculosis is often more complex and toxic with longer treatment time and poor treatment outcomes including treatment failure or death. Monitoring drug-resistant tuberculosis therapy including early identification of prognostic factors and close monitoring of body weight in resource-limited settings is crucial to ensure successful treatment. Therefore, this study was conducted to assess time to poor treatment outcome which is defined as the proportion of all patients who died or failed treatment and its predictors among drug-resistant tuberculosis patients on second-line anti-tuberculosis treatment in Amhara region, Ethiopia. Methods A retrospective cohort study was conducted on all patients who started drug-resistant tuberculosis therapy from September 1, 2010 through December 31, 2017, at the University of Gondar Comprehensive Specialized Hospital, Boru-Meda Hospital, and Debre-Markos Referral Hospital in Amhara Region, Ethiopia. Data were entered using Epi-data Version 3.1 and analyzed using R version 3.41 software. The survival time was estimated using Kaplan-Meier survival curve and the survival time between different categorical variables were compared using the log rank test. Event time ratio with 95% confidence interval (CI) and p-value less than 0.05 were used to measure the strength of association and to declare statistically significant predictors respectively. Results A total of 508 patients with a median age of 28.5 [IQR: 22-40] years were included in this study. The overall cumulative survival probability of patients at the end of 24 months was 79% [95% CI,75,84%]. Rate of body weight change [Adjusted time ratio (ATR) = 5; 95% CI: 3.2, 7.7], secondary and above level of education [ATR = 2.3;95% CI:1.2,2.9], being non-anemic [ATR = 2.8,95% CI:1.2,3.8], being non-diabetic [ATR = 3.4;95% CI:1.3,8.8], without clinical complications [ATR = 7.6;95% CI:4.2,13.9], HIV negative [ATR = 1. 94:95% CI:1.35,2.35] and residing in rural [ATR = 0.51,95% CI:0.30,0.86] were predictors of time to poor treatment outcomes. Conclusion The survival rate of tuberculosis patients was higher at end of follow up relative to other studies. However, poor treatment outcome was higher in early phase of therapy. Educational level, rural residence, HIV/AIDS, diabetes mellitus, previous treatment, clinical complication, rate of body weight change and smoking history were significant predictors of time to poor treatment outcome. Therefore, intervention programs should focus on the identified factors to improve survival time of drug-resistant tuberculosis patients.